Chế tạo vàng nano bằng phương pháp chiếu xạ - Hiến, Nguyễn Quốc; Phú, Đặng Văn; Kim Lan, Nguyễn Thị; Anh, Nguyễn Tuệ; Dung, Nguyễn Xuân; Du, Bùi Duy; Phương Phong, Nguyễn Thị; Cam, Bùi Duy (Vietnam Journal of Chemistry, 2014)
Gold nanoparticles were prepared by g-irradiation of HAuCl4 aqueous solution using chitosan as stabilizer. The particles have a Plasmon absorption band with maximum wavelength in the range of 520 - 534 nm. The average size of gold nanoparticles observed by transmission electron microscope (TEM) was of 25.3; 23.4 and 16.4 nm for 0.5; 1.0 and 2.0% chitosan respectively. The effect of Au3+concentration on the particle size and the stability of gold colloidal nanoparticles with storage time were also studied.